No differences in executive functions between female and male young talented football players - Lehmann, Jennifer; Pietsch, Stefanie (Frontiers in Psychology, 2025)
IntroductionResearch regarding the relationship between cognitive performance and sport performance in young talented football players has mainly been investigated in male athletes. Only few studies have addressed these aspects in female athletes. Thus, this quasi-experimental cross-sectional study aims to contribute to research addressing possible sex differences in the relationship of cognitive aspects in young talented football players during a selection assessment for a representative team and possible adjustments in this process or training processes in consideration of potential sex differences.MethodsTherefore, the participants were assessed using a general questionnaire, the Number Connection Test (ZVT), and a resilience questionnaire (1st session), as well as the 2-back test, the Flanker test, and the Switching task (computer-based, 2nd session). In total 59 male and 47 female athletes aged between 12 and 13 years were included.ResultsThe results of this study did not show any differences in executive function performance between female and male talented football players. Additionally, when examining potential differences between players selected for a representative team and those, who were not, no such differences were detected. Neither in general, nor sex-specific.DiscussionThe results suggest that further research is necessary to clarify whether there are sex differences among talented young football players and whether these differences play a role in the selection for a representative team.